FGF21 Acts Centrally to Induce Sympathetic Nerve Activity, Energy Expenditure and Weight Loss - Owen, Bryn M. (2014)
The mechanism by which pharmacologic administration of the hormone FGF21 increases energy expenditure to cause weight loss in obese animals is unknown. Here we report that FGF21 acts centrally to exert its effects on energy expenditure and body weight in obese mice. Using tissue-specific knockout mice, we show that βKlotho, the obligate co-receptor for FGF21, is required in the nervous system for these effects. FGF21 stimulates sympathetic nerve activity to brown adipose tissue through a mechanism that depends on the neuropeptide corticotropin-releasing factor. Our findings provide an unexpected mechanistic explanation for the strong pharmacologic effects of FGF21 on energy expenditure and weight loss in obese animals.